National Power Grid from Romania: An Approach to Energy Security Strategy - Fita, Daniel N.; Pasculescu, Dragos; Popescu, Florin G.; Grigorie, Emilia; Lazar , Teodora; Pupaza, Cristina (New Trends in Physical Science Research Vol. 3, 2022)
The National Power Grid is a critical component of the National Power System, containing critical infrastructures of national importance without which the national economy could not function, and its failure, whether complete or partial (black/brown-out), causes energy insecurity, a negative factor with devastating and catastrophic consequences for industrial, economic, and national security. Because the National Power Grid is of national strategic importance, it must be assessed and monitored on a continuous basis in terms of security risks in order to identify vulnerabilities. This assessment is also necessary from a European perspective, as Romania is connected to ENTSO-E (European Network of Transmission System Operators), which connects various power overhead lines from North to South, West to East, and even with Africa and Asia. . By knowing the vulnerabilities, one can automatically identify the dangers and threats to which it is subjected and engaged, being able to develop national/European measures or strategies for the protection and security of the critical infrastructures related to. For this reason, it is considered that the identification of vulnerabilities must become a pressing issue of national, and European energy security and be a useful tool for authorities to develop a energy strategy (short – long term) for the proper functioning of the National Power Grid and the national economy, because all sectors of the economy depend on electricity. The authors propose a National Energy Strategy 2021–2036 (short, medium, and long term) to address the identified weaknesses, with the goal of increasing energy and national security.